Symmetric and asymmetric volatility: Forecasting the Borsa Istanbul 100 index return volatility - Selma Öner; Hakan Öner (Financial Internet Quarterly, 2023)
The development of technology and the globalization of financial markets have increased the volatility in financial markets and caused the emergence of risks and uncertainties that have not been previously encountered. Since traditional econometric models cannot fully explain this vol- atility, nonlinear conditional variance models such as ARCH, GARCH, EGARCH and TARCH are used today. From this point of view, this study aims to determine the most explanatory model that fund managers who are considering investing in the Borsa Istanbul 100 (BIST 100) Index, and academicians doing research on this subject, can use in estimating the BIST 100 Index return volatility. For this purpose, ARCH and GARCH models, as symmetric models, and EGARCH and TARCH models, as asymmetric nonlinear conditional models, are included in the econometric analysis by using the end-of-day values of 2657 observations belonging to the 04.01.2010- 28.07.2020 period. According to the empirical results of the study, the TARCH model, which has the highest level of explanatory power, gives the most successful results among related models in revealing BIST 100 Index return volatility.
Keywords: C58; F30; F37; 330; ARCH models; symmetric volatility; asymmetric volatility